Androgen receptor polyglutamine expansion drives age-dependent quality control defects and muscle dysfunction. - Nath, S.R.; Yu, Z.; Gipson, T.A.; Marsh, G.B.; Yoshidome, E.; Robins, D.M.; Todi, S.V.; Housman, D.E.; Lieberman, A.P. (Journal of Clinical Investigation, 2018)
Skeletal muscle has emerged as a critical, disease-relevant target tissue in spinal and bulbar muscular atrophy, a degenerative disorder of the neuromuscular system caused by a CAG/polyglutamine (polyQ) expansion in the androgen receptor (AR) gene. Here, we used RNA-sequencing (RNA-Seq) to identify pathways that are disrupted in diseased muscle using AR113Q knockin mice. This analysis unexpectedly identified substantially diminished expression of numerous ubiquitin/proteasome pathway genes in AR113Q muscle, encoding approximately 30% of proteasome subunits and 20% of E2 ubiquitin conjugases. These changes were age, hormone, and glutamine length dependent and arose due to a toxic gain of function conferred by the mutation. Moreover, altered gene expression was associated with decreased levels of the proteasome transcription factor NRF1 and its activator DDI2 and resulted in diminished proteasome activity. Ubiquitinated ADRM1 was detected in AR113Q muscle, indicating the occurrence of stalled proteasomes in mutant mice. Finally, diminished expression of Drosophila orthologues of NRF1 or ADRM1 promoted the accumulation of polyQ AR protein and increased toxicity. Collectively, these data indicate that AR113Q muscle develops progressive proteasome dysfunction that leads to the impairment of quality control and the accumulation of polyQ AR protein, key features that contribute to the age-dependent onset and progression of this disorder.